A robust approach to hedging and pricing in imperfect markets - Hirbod Assa; Nikolay Gospodinov (Risks, 2017)
This paper proposes a model-free approach to hedging and pricing in the presence of market imperfections such as market incompleteness and frictions. The generality of this framework allows us to conduct an in-depth theoretical analysis of hedging strategies with a wide family of risk measures and pricing rules, and study the conditions under which the hedging problem admits a solution and pricing is possible. The practical implications of our proposed theoretical approach are illustrated with an application on hedging economic risk.
Keywords: G11; G13; C22; E44; 330; imperfect markets; risk measures; hedging; pricing rule; quantile regression